Profiling of elite male junior 50 m freestyle sprinters: Understanding the speed-time relationship - Morais, J. E.; Barbosa, T. M.; Silva, A. J.; Veiga, S.; Marinho, D. A. (Scandinavian Journal of Medicine & Science in Sports, 2022)
The aim of this study was to (1) analyze and compare the race performance and stability between the fastest and slowest male swimmers during the 50 m freestyle event, and (2) to understand the speed-time relationship in this race. The performances (start, clean swim, and finish) of 86 swimmers (divided into two tiers: best and poorest performances) who competed in the 50 m freestyle event in the 2019 long course LEN European Junior Championships were analyzed. The swimming speed presented a significant difference between the groups (tier #1 vs tier #2) in all sections of the race, in which the start (S0-15 m: p < 0.001, d = 1.64) and finish sections (S45-50: p < 0.001, d = 1.63) showed the greatest differences. Significant variances over the race sections were noted for both groups in all variables, in which the swimming speed was the variable with the highest variance (tier #1: p < 0.001, ?2 = 0.72; tier #2: p < 0.001, ?2 = 0.82). Both groups exhibited a similar normative stability, with the fastest swimmers tending to be the best in all sections. The fit analysis produced a cubic speed-time relationship. Notwithstanding, junior swimmers who raced the 50 m freestyle can be considered to have an all-out pacing. This information is of paramount importance for coaches and swimmers to understand the intra-lap race performance in this short event.